Some geotechnical properties and damping ratio of clay nanocomposites - Majedi, Payam; Akbulut, Suat; Albayrak, Zeynep Nese Kurt (ACADEMIC PUBLICATION COUNCIL, 2019)
Natural clays soils are commonly used in dams, landfills, nuclear plants, etc. as an impermeable component or protecting liner. However, there could be permanent damage in structural elements due to the problems such as swelling, settlement, and heaving of these soils because of varieties in water contents over time. To remove these issues, stabilization of natural clay soils by the use of chemical additions is a prevalent subject of research. Recently, clay polymer interactions are commonly used for the improvement of nanocomposites. In addition, hydrophobic organoclays are preferred to eliminate the water affinity of clay nanocomposites. In this research, to improve damping ratio of clay liners, clay-nanocomposites are obtained from a hydrophobic organoclay, interacting with different concentrations of the latex polymer. Some geotechnical properties of these nanoclay-composites such as specific gravity, compaction parameters, unconfined compressive strength, and swelling pressure have been investigated. Additionally, damping ratios of these clay-nanocomposites are determined with a computer-based and multi-channel analysis system. pulse vibration measurement system. The test results found that specific gravities, maximum dry unit weights, unconfined compressive strengths. and swelling pressures of clay-nanocomposite samples decrease with the increase in latex concentration. On the other hand, damping ratios of samples are increased with latex concentration. The obtained results indicate that the damping ratio for provided nanocomposite in dry mode and in wet mode was increased from 1.08% (without additives) to 7.14% (including 20% Latex) and from 5.06% (without additives) to 8.47% (including 20% Latex), respectively.
Keywords: Clay-nanocomposites; contact angle; damping ratio; geotechnical properties; hydrophobic organoclay; unconfined compressive strength; SILICATE NANOCOMPOSITES; POLYMER; STRENGTH; STARCH; Engineering